2021
DOI: 10.1017/s0030605321000223
|View full text |Cite
|
Sign up to set email alerts
|

LeopardPanthera pardusdensity and survival in an ecosystem with depressed abundance of prey and dominant competitors

Abstract: The leopard Panthera pardus is in range-wide decline, and many populations are highly threatened. Prey depletion is a major cause of global carnivore declines, but the response of leopard survival and density to this threat is unclear: by reducing the density of a dominant competitor (the lion Panthera leo) prey depletion could create both costs and benefits for subordinate competitors. We used capture–recapture models fitted to data from a 7-year camera-trap study in Kafue National Park, Zambia, to obtain bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 70 publications
(153 reference statements)
0
5
0
Order By: Relevance
“…This leopard density estimate represents one of few from WMAs (i.e., 17 of 161 estimates reviewed), falling among the lower end of densities throughout Africa or Asia and below records in similar mixed forest and seasonal floodplain habitats (e.g., 4.80–8.38, Tembe Elephant Park, South Africa, Ramesh et al, 2017, Rogan et al, 2019; 3.34–7.89, Kafue National Park, Zambia, Vinks et al, 2021). However, this relatively low estimate may be typical of semiarid environments (1.18, Devens et al, 2019; 2.20, Faure et al, 2021; 1.53–1.62, Müller et al, 2022; 1.83, Portas et al, 2022) and human‐impacted landscapes (2.49, Balme et al, 2010; 2.7, Henschel et al, 2011; 1.9, Davis et al, 2020; 0.66, Power et al, 2021; 0.7–1.8, Loveridge et al, 2022).…”
Section: Discussionmentioning
confidence: 92%
“…This leopard density estimate represents one of few from WMAs (i.e., 17 of 161 estimates reviewed), falling among the lower end of densities throughout Africa or Asia and below records in similar mixed forest and seasonal floodplain habitats (e.g., 4.80–8.38, Tembe Elephant Park, South Africa, Ramesh et al, 2017, Rogan et al, 2019; 3.34–7.89, Kafue National Park, Zambia, Vinks et al, 2021). However, this relatively low estimate may be typical of semiarid environments (1.18, Devens et al, 2019; 2.20, Faure et al, 2021; 1.53–1.62, Müller et al, 2022; 1.83, Portas et al, 2022) and human‐impacted landscapes (2.49, Balme et al, 2010; 2.7, Henschel et al, 2011; 1.9, Davis et al, 2020; 0.66, Power et al, 2021; 0.7–1.8, Loveridge et al, 2022).…”
Section: Discussionmentioning
confidence: 92%
“…While camera traps in Kavango-Zambezi Transfrontier Conservation Area detected multiple cases of snared lions and spotted hyenas, only a single leopard out of 386 identified individuals was noted as having a possible snare scar (Loveridge et al, 2020). Leopards with non-lethal snare injuries were encountered in NKNP by Schuette et al (2018), and yet a subsequent (2013-2019) camera trap study to investigate leopard mortality in NKNP (Vinks et al, 2021b) detected no snare injuries among 63 identified individuals. Similarly, a camera trap study of leopards in LV did not detect any snare injuries among 43 identified individuals and concluded that snared leopards in LV were uncommon relative to snared lions and wild dogs (Rosenblatt et al, 2016).…”
Section: Discussionmentioning
confidence: 98%
“…There are several potential explanations for the relatively lower frequency of snare injury found in leopards. Although leopards occur in the same regions and habitats as do other large carnivores, e.g., lion, spotted hyena, and wild dog Lycaon pictus for which snaring bycatch is well-known (Becker et al, 2013a;Loveridge et al, 2020;Vinks et al, 2021b), leopards may be less likely to encounter a snare due to behavioral differences. However, leopards feed on ungulate species targeted by wire-snare poachers (Henschel et al, 2011;Creel et al, 2018;Strampelli et al, 2018), and may scavenge on animals killed in snares (Strampelli et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We therefore assume that a minimum of 56 IDs with at least 15-18 identified individuals represent the threshold necessary for modelling sex-specific Leopard density. A higher sample size facilitates modelling sex-specific differences in detectability and spatial patterns (Goldberg et al 2015;Kittle et al 2021;Vinks et al 2021), whereas a smaller sample size is insufficient for this model (Strampelli et al 2020).…”
Section: Leopard Densitymentioning
confidence: 99%